Implications of Falsifying Authentic Data in Deed of Sale & Purchase on Certificate of Building Use Rights (SHGB) - Teguh Eko Saputro; Ira Alia Maerani; Taufan Fajar Riyanto (Sultan Agung Notary Law Review, 2021)
PPAT is a public official who is given the authority to make deeds as evidence that certain legal actions regarding land rights have been carried out in court. One type of deed made before the PPAT is the deed of sale and purchase (AJB). AJB made before PPAT is a formulation of the will of the parties contained in it. The notary is required to be responsible for the deed he has made, sometimes the deed made before the notary contains false information, fraud and even untruth and is often subject to Articles 263, 264, and 266 in conjunction with Article 55 of the Criminal Code. However, if it is found that there are violations committed by PPAT criminally, criminal sanctions can be imposed according to the Criminal Code. This research was conducted through a normative juridical approach, namely an approach to problems formulated by studying the provisions of laws and regulations relating to problems and comparing them with the application of laws and regulations. Data analysis was carried out by collecting primary and secondary data. Data analysis was evaluated qualitatively using interpretation and legal logic so as to obtain or strengthen an existing picture to answer problems based on laws and regulations using a deductive method. The results of this study indicate that the legal implications of falsifying authentic data on sale and purchase deeds made by PPAT are that the deed only has legal force as an underhand deed and the authentic deed can be canceled if the party claiming can prove it in court in court. The responsibility of PPAT who commits falsification of authentic data in making a deed of sale and purchase, can be held accountable before the law because his actions cause harm to others. In this case the forgery of the deed committed by the PPAT/Notary San Smith in a criminal manner, criminal sanctions can be imposed in accordance with the Criminal Code (KUHP), namely Article 266 Paragraph (1) in conjunction with Article 55 Paragraph (1) 1st of the Criminal Code with threats participated in entering false information and there were losses resulting from a forged deed, so that PPAT San Smith was sentenced to 1 year in prison in the Medan District Court Decision No. 3036/Pid.B/2009/PN.Mdn. Efforts are being made to overcome the problem of falsifying authentic data on the sale and purchase deeds made by PPAT, namely providing legal protection with the following steps: (a) formulating specific rules regarding the limitations of notary criminal liability in UUJN.